Professionalism among multicultural medical students in the United Arab Emirates - Abdulrahman, Mahera (Med Educ Online, 2017)
Background: Moral competencies and ethical practices of medical professionals are among the desired outcomes of academic training. Unfortunately, academic dishonesty and misconduct are reported from medical colleges across the world. This study investigates the level of academic dishonesty/misconduct among multicultural medical students. Objective: The aim of this study is to investigate the level of academic dishonesty/misconduct among multicultural medical students. Design: Validated and customized version of Dundee Polyprofessionalism Inventory-1 detailing lapses of professionalism in undergraduate health professions education was used to determine the perceived prevalence and self-reported lapses of academic integrity in this study. Results: This study shows that the majority (458/554, 83%) of medical students have admitted to acts of academic dishonesty mentioned in the questionnaire. Approximately 42% (231/554) of the students have given proxy for attendance and 71% of them considered this as an offense. Similarly, 12% (66/554) have copied from the record books of others, and 86% (477/554) have considered it unethical. In addition, 5% (28/554) of the students revealed forging a teacher’s signature in their record or logbooks, with 16% (91/554) of them reporting that they have seen others forge signatures. Conclusion: This is the first multi-center, multi-cultural and multi-ethnic study involving a large number of participants that addresses academic professionalism among medical students in the Middle East. Certainly, the paucity of data limits definitive conclusions about the best approach to prevent academic misconduct in the UAE medical schools. Yet, the results of our study are anticipated not only to benefit the UAE but also to find application in the Arab world, with similar medical school programs, values, culture and tradition.